The impact of Covid-19 pandemic on the institutional change in developing countries - Legiędź, Tomasz (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The Covid-19 pandemic is having a critical impact on economies, especially in developing countries. Such a serious external shock affects the distribution of economic rents, thus leading to potentially large institutional changes. Naturally, in the short term we are dealing with an economic crisis and a restriction of civil liberties in both autocratic and democratic countries, however, it is not known what the dynamics of institutional changes will be in the longer run. Aim: The main purpose of the article is to answer if the Covid-19 pandemic becomes a turning point that will determine the institutional system in developing countries for the next few decades. The first part of the article outlines the theory of institutional change, with particular emphasis on the role of external shocks. The next section presents studies on the socioeconomic impact of two major epidemics: The Black Death and the Great Influenza Pandemic. The third part conducts an assessment as to what extent the current pandemic may affect institutions in developing countries, by reference to the example of two countries: Tunisia and Cambodia. The analysis is conducted from the perspective of the new institutional economics. Results: If we look at the experiences from previous pandemics, current events and refer to the literature on the theory of institutional change, we can conclude that significant institutional changes caused by Covid-19 are unlikely. The process of institutional change is characterized by a specific complexity and changing dynamics. Nonetheless, it is the internal factors, reflecting the actions of people trying to maximize the benefits, which are the main cause of change in an institutional system. Therefore, the Covid-19 pandemic is more likely to strengthen the endogeneity of the process of institutional change, rather than change its course.